The influence of Internet shopping and use of credit cards on gender differences in compulsive buying. Issue 1 (8th March 2022) - Xu, Changqin; Unger, Alexander; Bi, Chongzeng; Papastamatelou, Julie; Raab, Gerhard
Abstract : Purpose: Buying behavior has been significantly altered by technological developments as a result of the rise of the Internet. Online buying behavior is also inextricably linked to electronic payment systems, such as credit cards. This paper investigates how credit-card systems and online shopping increases compulsive buying of female and male consumers. Design/methodology/approach: In the current study, the authors tested the influence of credit card possession and the role of Internet shopping on gender differences in compulsive buying in a representative German sample ( n = 1, 038). Binary logistic regression analysis and moderator analysis were applied. Findings: As predicted, Internet shopping increased compulsive buying, but the association was the same for females and males. Further, credit card possession moderated the effect of gender on compulsive buying, with females showing a higher proneness to compulsive buying. Originality/value: This research, which is based on a representative population study, contributes to the understanding of the role of credit cards and the one of online shopping in developing compulsive buying patterns among female and male consumers.